Can mesenchymal stem cell survive in hydroxyapatite sulphate? (Faculty of Medicine Universitas Indonesia, 2012)
Background: Many studies have reported the role of Mesenchymal Stem Cells (MSC) in treating fractures. In case with bone defect, fracture healing needs not only osteogenic but also osteoconductive component (scaffold). Hydroxyapatite calcium sulphate (HA-CaSO4) being widely used as bone void filler, may serve as scaffold for MSC. However, the effect of this scaffold to the viability of MSC has not been evaluated before.Methods: MSC were isolated from the iliac marrow of a Giant Flamish rabbit, and expanded in DMEM using histogradient density. After one week, they were sub-cultured in a 25cc TC flask (passage 1) and have the medium replaced every 3 days. During the subculture, we embedded a HA-CaSO4 pellet into the flask. The cells were evaluated under inverted microscope at a weekly interval.Results: At the first week, MSC are difficult to be identified in microscope due to the large number of HA-CaSO4 crystals. By the third week however MSC have grown and the HA-CaSO4 crystals can readily be washed off by medium replacement. By the fourth weeks, MSC can be still seen on microscope.Conclusion: HA-CaSO4 could serve as a good scaffold due to its pellet shape and easily absorbed, thus providing revascularization which is essential for bone healing.In addition, HA-CaSO4 does not interfere with MSC survival. (Med J Indones 2012;21:8-12)Keywords: Fracture healing, Hydroxyapatite Calcium Sulphate (HA-CaSO4), Mesenchymal Stem Cells (MSC)